Positive and negative roles of an initiator protein at an origin of replication. - Filutowicz, M (1986)
The properties of mutants in the pir gene of plasmid R6K have suggested that the pi protein plays a dual role; it is required for replication to occur and also plays a role in the negative control of the plasmid copy number. In our present study, we have found that the pi level in cell extracts of Escherichia coli strains containing R6K derivatives is surprisingly high (approximately equal to 10(4) dimers per cell) and that this level is not altered in cells carrying high copy number pir mutants. The wild-type and a high copy mutant (Cos405) pir gene were inserted downstream of promoters of different strengths to measure the copy number of an R6K gamma replicon as a function of a 1000-fold range of intracellular pi concentrations. The data demonstrate that reducing the intracellular level of pi to 5% of its normal value can result in a substantial increase in copy number of a gamma origin replicon and that a pi level less than 1% of normal is still permissive for replication. Conversely, increasing the pi level even a few-fold above normal results in a marked inhibition of replication of plasmids containing a single, two, or all three of the R6K origins (alpha, beta, and gamma). We have also shown that the replication inhibition mediated by excess pi is greatly reduced by the pir405 Cos mutation. These results demonstrate that the total level of pi protein is not rate-limiting for a gamma replicon. We have also determined the sensitivity of the pir gene promoter to a wide range of pi concentrations. The activity of this promoter is stimulated by very low pi levels and is almost entirely inhibited when the protein is overproduced 2-fold.